Chicken Embryo Model Perspective : Novel and Relevant Models Immunity-Based Research: A Systematic Review - Fadhli Rahman Fauzi; Maslichah Mafruchati (JURNAL RISET RUMPUN ILMU HEWANI, 2025)
Dysregulation of the immune system is associated with many medical conditions, including: Cardiovascular disease, diabetes, cancer. Most popular model today. In biomedical research, rodents, despite the many advantages they offer, there are also many drawbacks to its use. Recently, another in vivo model, the chicken Embryos and their chorioallantoic membranes are resurfaced for a variety of uses. This model includes cost-effectiveness, time-efficiency, Easier to use. This review describes how to use chicken embryos. As a model for immune-based research because it gradually develops the embryonic immune system, Systems functionally similar to humans. This study examined mainly intended to describbe the immune system of birds, highlighting the differences and similarities with the human immune system A system containing a repertoire of lymphoid tissue, immune cells, and other important functions. A literature search was carried out systematically through the PubMed, NCBI, Google Scholar databases using keywords, namely, “Chicken embryo model, Perspective, Novel and relevant models Immunity, based research”. Based on these keywords, 21350 articles were obtained and 50 articles that meet the inclusion and exclusion criteria were selected. Those helped to describe general in-ovo immune ontogeny. Future studies are suggested to better tailor the use of chicken embryo models for testing carrying out specific experimental hypotheses or preclinical studies.